More procedures, more efficiency: optimizing operating room during the phase of learning curve—experience of first 100 robotic bariatric procedures in a single center - Nicolas, Zucchini; Eleonora, Locci; Enrico, Moroni; Giovanni, Fantola (Journal of robotic surgery, 2025)
Robotic bariatric surgery (RBS) is increasingly adopted worldwide. This study aims to evaluate the implementation and evolution of RBS at a high volume center over five years, focusing on operative time (OT), operating room (OR) efficiency, and cost outcomes. A prospective analysis was conducted on patients undergoing elective RBS between July 2021 and March 2025 at ARNAS G. Brotzu, Cagliari. Metrics included OT, OR session time, and surgical volume. Variables analyzed included OT, OR session time, and surgical volume. Efficiency metrics such as overall OR efficiency, defined as OR session time/OT (Eff1), and robotic console utilization, defined as OR session time/console time (Eff2) were derived. Cost analysis incorporated OR activation time, surgeon and material costs. Statistical analyses included t -tests, Pearson’s correlation, and linear regression. 100 robotic-assisted procedures were recorded. Robotic adoption increased from 4.06% in 2021 to 38.98% in 2025. A learning curve (LC) was identified, with a significant OT reduction after the first 34 Roux-en-Y gastric bypass cases ( p = 0.001). Full robotic manual anastomosis showed a notable cost decrease in later cases ( p < 0.0001). Increased surgical volume correlated with both reduced OT ( r = – 0.58) and improved Eff1 ( r = – 0.49, p = 0.005). However, Eff2 changes were not statistically significant ( r = – 0.31, p = 0.09), underscoring the need for team-wide coordination. RBS in high-volume centers enhance OR efficiency and cost-effectiveness over time. The LC, surgical volume, and institutional workflows were key factors in optimizing efficiency, highlighting the importance of a collective LC for the entire surgical team.